Toward a Vision of Sustainable University: Linkages between Commitment and Practices - Qayim, Ibnul; Utami, Anisa Dwi; Putra, Heriansyah; Slamet, Alim S; Mardiana, Rina; Dwiyanti, Fifi Gus (Universitas Diponegoro, 2024)
Sustainability management plays a significant role in higher education. Development of a sustainable university involves integrating environmental, social, and economic considerations into various aspects of its operations, including campus infrastructure, curriculum, research, and community engagement. This urgently requires a strong commitment as a driving force behind sustainable initiatives, guiding actions, decisions, and investments toward achieving sustainability goals. IPB University as one of the most prominent universities in Indonesia is not only committed to becoming a sustainable university but also consistent in developing strategic plans to pursue its vision. Guided by this vision, IPB University has specifically established the Sustainable Campus Development Office (SCDO) to devise comprehensive sustainability plans outlining its goals, targets, and strategies for reducing environmental impact, promoting social equity, and ensuring economic viability. While it is still on progress, this commitment has played a significant role in encouraging sustainability practices at the university. It provides a foundation for leadership, governance, resources allocation, curriculum integration, student engagement, community partnerships, monitoring, reporting, and continuous improvement toward achieving sustainability goals. In addition, the university has established several sustainability values as guidance and indicators for maintaining sustainable practices. Integrating values and commitment is thus critical to realizing sustainable practices from generation to generation.